International Experience of Agricultural Land Market Turnover Regulation - L’ubov Kuzmenko (Наукові записки НаУКМА: Економічні науки, 2021)
The land market in Ukraine is currently being formed. Therefore, it is now especially important to master the experience of using the mechanisms of regulation of this important market, which have undergone a long and successful testing in foreign countries. The article reveals the main directions of international experience in regulating the market of agricultural land. To ensure the optimal distribution of land among users and for the efficient functioning of the land market in most countries of the world, land policy is structured in such a way that agricultural land is cultivated by those who are able to ensure its most productive use. The article analyzes the possibility of applying this experience in Ukraine on the basis of generalization of modern foreign practice. The agricultural land, in contrast to the land for industry, transport and other industries, is the main means of production. The article notes that the current model of state regulation of the land market can lead to the monopolization of such markets and the acquisition of agricultural land by large corporations. There are considered the opinions of various authors on this issue, and has defined the need to form the main aspects necessary for the efficient use of land resources. The example of individual countries shows that the lack of active state intervention in market turnover has led to the monopolization of agricultural land by large corporations. It is concluded that at the present stage of implementation of the policy that ensures the efficiency of land use in agriculture, the state should strengthen the functions of regulating land use processes. There were some specific proposals for improving the system of regulation of land relations in agriculture, which should play a progressive role in the further development of the state.